Ecuaciones e inecuaciones en el conjunto de nmeros enteros - Rumiche Villalta, Cynthia Consuelo (2019)
Worldwide education systems have been implementing changes in order to improve the_x000D_ quality of student learning. International tests indicate that one of the areas with low results is mathematics. In Peru, the Ministry of Education has implemented the problem-solving approach to overcome traditional education, it is intended that the student build their own learning under the expert mediation of the teacher In this paper, I present a learning session called "Equations and inequations with integer numbers" designed under the problem-solving approach and related to the competition "Solve problems of regularity, equivalence and change" of the Mathematical Area, with students of First Secondary grade This proposal provides the combination of area capabilities_x000D_ The proposal has taken into account the pedagogical and didactic processes of the area, as well as the guidelines provided by the Ministry of Education for the development of_x000D_ competencies, from a formative evaluation approach, which constitute a pedagogical andtheoretical basis.